Dissolving Precipitated Asphaltenes Inside Oil Reservoirs Using Local Solvents - Farhan, Laith Warid; Almahdawi, Faleh H. M.; Hammadi, Adel Sherif (Iraqi Journal of Chemical and Petroleum Engineering, 2020)
There are several oil reservoirs that had severe from a sudden or gradual decline in their production due to asphaltene precipitation inside these reservoirs. Asphaltene deposition inside oil reservoirs causes damage for permeability and skin factor, wettability alteration of a reservoir, greater drawdown pressure. These adverse changing lead to flow rate reduction, so the economic profit will drop. The aim of this study is using local solvents: reformate, heavy-naphtha and binary of them for dissolving precipitated asphaltene inside the oil reservoir. Three samples of the sand pack had been prepared and mixed with a certain amount of asphaltene. Permeability of these samples calculated before and after mixed with asphaltenes. Then, the permeability of samples calculated after solvents injection into that porous media. After that, all the values of samples permeability converted to average permeability damage compared with the pure samples. The results show the average permeability damage of samples that mixed with 20 gm was 24 %, but after reformate injected reduced to 14 %. After injected heavy naphtha to porous media, the average permeability reduced only to 17%. The binary solvent had been prepared from reformatted mixed with heavy naphtha gained the best results because it dropped the average permeability damage to 10%.